Foreign Portfolio Investment and Stock Market Volatility in India - De, Suddhasanta; Chakraborty, Tanupa (Indian Journal of Finance, 2015)
Although, it is a generally held belief that foreign portfolio flows benefit the economies of recipient countries, policy-makers worldwide have perennial discomfort about such investments. Such portfolio flows are widely termed as "hot money," given its notorious volatility compared to other forms of capital flows as foreign investors make sudden and concerted withdrawals of portfolio investments at the faintest smell of trouble in the host country, thereby accelerating and magnifying the inconspicuous problem of the downfall in stock prices, often leading to disastrous consequences to the host economy. The discussion is often emphasized by the financial press due to the visible evidence of their contemporaneous nature at times of economic crisis. Relationship between foreign institutional ownership and volatility is largely inconclusive. Although the literature in business newspapers and also some previous empirical studies suggest that institutions tend to destabilize prices by increasing turnover levels, there are some good reasons to believe that higher levels of institutional ownership could be negatively related to volatility. In this present study, using firm-level Indian panel data from 2003 to 2013, we analyzed the association between stock's return volatility and their FII holdings in a VAR framework. The results showed that no significant causal relationship exists between the two variables.